Enhancing stroke risk prediction in patients with transient ischemic attack: insights from a prospective cohort study implementing fast-track care - Barone, Valentina; Foschi, Matteo; Pavolucci, Lucia; Rondelli, Francesca; Rinaldi, Rita; Nicodemo, Marianna; D’Angelo, Roberto; Favaretto, Elisabetta; Brusi, Carlotta; Cosmi, Benilde; Degli Esposti, Daniela; D’Addato, Sergio; et al. (Frontiers in Neurology, 2024)
Background and aims: Fast-track care have been proved to reduce the short-term risk of stroke after transient ischemic attack (TIA). We aimed to investigate stroke risk and to characterize short-and long-term stroke predictors in a large cohort of TIA patients undergoing fast-track management.Methods: Prospective study, enrolling consecutive TIA patients admitted to a Northern Italy emergency department from August 2010 to December 2017. All patients underwent fasttrack care within 24 hours of admission. The primary outcome was defined as the first stroke recurrence at 90 days, 12 and 60 months after TIA. Stroke incidence with 95% confidence interval (CI) at each timepoint was calculated using Poisson regression. Predictors of stroke recurrence were evaluated with Cox regression analysis. The number needed to treat (NNT) of fast-track care in preventing 90-day stroke recurrence in respect to the estimates based on baseline ABCD2 score was also calculated.We enrolled 1035 patients (54.2% males). Stroke incidence was low throughout the follow-up with rates of 2.2% [95% CI 1.4%-3.3%] at 90 days, 2.9% [95% CI 1.9%-4.2%] at 12 months and 7.1% [95% CI 5.4%-9.0%] at 60 months. Multiple TIA, speech disturbances and presence of ischemic lesion at neuroimaging predicted stroke recurrence at each timepoint. Male sex and increasing age predicted 90-day and 60-month stroke risk, respectively. Hypertension was associated with higher 12-month and 60-month stroke risk.No specific TIA etiology predicted higher stroke risk throughout the follow-up. The NNT for fast-track care in preventing 90-day stroke was ] in the overall cohort and 6.8 [95% CI 4.6-13.5] in patients with baseline ABCD2 of 6 to 7.Our findings support the effectiveness of fast-track care in preventing both short-and long-term stroke recurrence after TIA. Particular effort should be made to identify